IMPLEMENTASI PROGRAM REHABILITASI RUMAH TIDAK LAYAK HUNI PERSPEKTIF SIYASAH SYAR’IYYAH - Oktapiani, Tenri; Mapuna, Hadi Daeng (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2022)
This study aims to find out how the implementation of the Uninhabitable House Rehabilitation Program in the Selayar Islands Regency in the Perspective of Siyasah Syar’iyyah. This research is a field research with a juridical approach and a syar’i approach. The rehabilitation program for uninhabitable houses launched by the Selayar Islands Regency Government has been implemented well and has a positive impact, especially for underprivileged residents. As a priority program, the rehabilitation of uninhabitable houses is carried out through several stages, starting from the planning, data collection, and implementation stages. Rehabilitation of uninhabitable houses is a program that provides benefits because it directly touches the basic needs of underprivileged residents.